To publish, publish, publish. Where it is scientific ethics? - Honório Silva Santos, Patrícia; Pires Dutra, Laisla; da Silva Sena, Edite Lago; Donha Yari, Sergio; Silva de Oliveira Boery, Rita Narrimam (Acta Bioethica, 2017)
The scope of this study was to analyze the existing literature on scientific fraud and their bioethical issues. Type of integrative literature review and the data collected in the Lilacs and SciELO databases, using descriptors, scientific fraud and plagiarism. Found 7 articles that met the inclusion criteria. The results were categorized into three themes, History of scientific fraud; Scientific fraud and bioethical implications; and adopted measures. It was concluded that researchers and academics should always be reviewing their ethical stances in the face of scientific publications. There are still gaps about scientific fraud, particularly relating them to bioethical issues. Thus, this study may contribute to the reflections on the theme.